The long-term implications of an after-school STEM mentoring program: the perspectives of former STEM undergraduate student mentors - Martínez Oquendo, Pamela (International journal of mentoring and coaching in education, 2025)
PurposeThe purpose of this study was to make sense of the individual perspectives of former undergraduate student mentors from science, technology, engineering, and mathematics (STEM) fields who took part in an after-school STEM mentoring program. The study examined the following research questions: (1) How do former undergraduate student STEM mentors interpret and give meaning to their after-school STEM mentoring experiences? (2) In what way can an after-school STEM mentoring experience lead to a deeper understanding of the long-term implications of a STEM mentorship program?Design/methodology/approachThe sample comprised 21 former undergraduate STEM mentors. The study was guided by the methods of content analysis and repertory grid (RepGrid), with data collected via highly structured interviews. Eight elements were pre-selected for the RepGrid to elicit constructs from participants. These include (1) mentoring, (2) teaching, (3) research, (4) career, (5) workforce, (6) Nebraska STEM for you (NE STEM 4U), (7) networking, and (8) communication. The researcher employed content analysis for cross-case analysis and used interpretative clustering to analyze nuanced similarities and differences among participants. Personal construct theory was used to understand how former STEM mentors made sense of their experiences.FindingsThe results highlight the diversity of viewpoints among participants, as well as their connections to various career paths, communication strategies, and mentorship styles. These insights contribute to a deeper understanding of how STEM mentorship experiences can be tailored to the experiences of mentees. The study stresses the significance of clear communication in STEM and advises professionals to avoid excessive technical jargon to convey complex ideas. Overall, the study provides valuable insights into the motivations, perspectives, and benefits of former undergraduate mentors. Ultimately, recognizing how these factors impact STEM mentoring programs is vital for the long-term success and advancement of the STEM pipeline.Research limitations/implicationsThe study has several limitations, including the inclusion of participants lacking knowledge or experience with the eight elements used in the RepGrids. While participants had completed a bachelor’s degree in a STEM field, not all had pursued advanced schooling or careers that required knowledge or implementation of research.Practical implicationsFindings underscore the importance of acknowledging the diverse career paths within STEM fields to understand participants’ perspectives toward mentorship. Considering the incorporation of STEM mentorship within regular school hours and making it a graduation prerequisite could enhance student participation and advancement. Integrating STEM outreach programs into higher education curricula could facilitate the development of essential professional skills (e.g. critical thinking, problem-solving) among STEM undergraduate students. These implications highlight the importance of diverse mentorship styles and professional skills to foster a more inclusive STEM workforce.Originality/valueThe study focused on the individual perspectives of participants rather than employing a thematic analysis.